Fe/Co bimetallic nanoparticles embedded in MOF-derived nitrogen-doped porous carbon rods as efficient heterogeneous electro-Fenton catalysts for degradation of organic pollutants. (September 2021) - Hu, Tong; Deng, Fengxia; Feng, Haopeng; Zhang, Jingjing; Shao, Binbin; Feng, Chengyang; Tang, Wangwang; Tang, Lin
Highlights: A novel heterogeneous electro-Fenton catalyst Fe2 Co1 /NPC was successfully synthesized. The system was effective for degradation of multiple organic pollutants. Fe2 Co1 /NPC catalyst exhibited good stability and reusability in four consecutive runs. Satisfactory performance in treatment of various real water matrix was achieved. The associated mechanism and possible tetracycline degradation pathways were proposed. Abstract: Developing efficient heterogeneous electro-Fenton (hetero-EF) catalysts for degradation of organic pollutants has triggered great interests. In this work, a novel hetero-EF catalyst, Fe/Co bimetallic nanoparticles embedded in MOF-derived nitrogen-doped porous carbon rods (Fe2 Co1 /NPC), was successfully synthesized in a facile manner for effective degradation of multiple organic pollutants including tetracycline (TC), chloramphenicol, ciprofloxacin, diclofenac sodium and sulfamethoxazole. Particularly, the Fe2 Co1 /NPC hetero-EF system achieved TC removal ratio of 91% within 60 min and mineralization efficiency of 90.3% within 240 min under neutral conditions, and exhibited good stability and reusability in consecutive cycling tests with low leaching of iron and cobalt. The mechanism exploration indicated that TC was primarily oxidized by OH and O2 – radicals, and the synergistic effects of nitrogen-doped porous carbon support and optimized Fe/Co bimetallic species endowed Fe2 Co1 /NPC with high catalytic performance in a wide pH range. The possible pathways for the mineralization of TC were also deduced. Furthermore, the Fe2 Co1 /NPC hetero-EF system achieved satisfactory performance in the treatment of real water matrix including tap water, river water and urban wastewater, suggesting its good application prospect. Graphical abstract: Image, graphical abstract